A percolation-based micromechanical model for elastic stiffness and conductivity of foam concrete - Wang, Fengjuan; Xin, Zhongyi; Jiang, Jinyang; Sui, Shiyu (Frontiers in Physics, 2023)
Void morphology effect on percolation and even physico-mechanical performance of foam concrete is of great interest in the evaluation of service-life of civil and hydraulic infrastructures. For experiments, it is a huge challenge to quantify the percolation threshold of voids affected by their morphologies, and the dependence of elastic modulus and conductivity of foam concrete on void configurations. In this work, we focus on the prolate spheroidal void morphologies with the aspect ratios of 2.5 and 2, following the microscopic measurements reported in the literature. A numerical framework is developed to capture the percolation threshold characterized by the critical porosity of voids with both morphological types. For the verification purpose, Measurement on the critical porosity of spherical voids using the present framework as a benchmark is compared against the percolation threshold of monodisperse overlapping spheres reported in literature. Furthermore, this work proposes a simple and powerful percolation-based micromechanical model for precisely predicting the effective elastic modulus and thermal conductivity of foam concrete. It can be convinced of a general micromechanical framework to elucidate the intrinsic relationship of void morphology and percolation to the physico-mechanical properties of concrete. The present framework is capable of tailoring physical and mechanical properties through void configuration and enable foam concrete design and multifunctional applications.